Antiplasmodial and Antioxidant Isoquinoline Alkaloids from Dehaasia longipedicellata - Leong, K.H. (Thieme E-Journals, 2014)
The crude extract of the bark of Dehaasia longipedicellata exhibited antiplasmodial activity against the growth of Plasmodium falciparum K1 isolate (resistant strain). Phytochemical studies of the extract led to the isolation of six alkaloids: two morphinandienones, (+)-sebiferine (1) and (-)-milonine (2); two aporphines, (-)-boldine (3) and (-)-norboldine (4); one benzlyisoquinoline, (-)-reticuline (5); and one bisbenzylisoquinoline, (-)-O-O-dimethylgrisabine (6). Their structures were determined on the basis of 1D and 2D NMR, IR, UV, and LCMS spectroscopic techniques and upon comparison with literature values. Antiplasmodial activity was determined for all of the isolated compounds. They showed potent to moderate activity with IC50 values ranging from 0.031 to 30.40 µM. (-)-O-O-dimethylgrisabine (6) and (-)-milonine (2) were the two most potent compounds, with IC50 values of 0.031 and 0.097 µM, respectively, that were comparable to the standard, chloroquine (0.090 µM). The compounds were also assessed for their antioxidant activities with di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium (IC50 = 18.40-107.31 µg/mL), reducing power (27.40-87.40 %), and metal chelating (IC50 = 64.30 to 257.22 µg/mL) having good to low activity. (-)-O-O-dimethylgrisabine (6) exhibited a potent antioxidant activity of 44.3 % reducing power, while di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium and metal chelating activities had IC50 values of 18.38 and 64.30 µg/mL, respectively. Thus it may be considered as a good reductant with the ability to chelate metal and prevent pro-oxidant activity. In addition to the antiplasmodial and antioxidant activities, the isolated compounds were also tested for their cytotoxicity against a few cancer and normal cell lines. (-)-Norboldine (4) exhibited potent cytotoxicity towards pancreatic cancer cell line BxPC-3 with an IC50 value of 27.060 ± 1.037 µM, and all alkaloids showed no toxicity towards the normal pancreatic cell line (hTERT-HPNE).